Using Heterogeneous Networks to Improve Energy Efficiency in Direct Coherence Protocols for Many-Core CMPs - Ros, Alberto; Fernández-Pascual, Ricardo; Acacio, Manuel E. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
Direct coherence protocols have been recently proposed as an alternative to directory-based protocols to keep cache coherence in many-core CMPs. Differently from directory-based protocols, in direct coherence the responsible for providing the requested data in case of a cache miss (i.e., the owner cache) is also tasked with keeping the updated directory information and serializing the different accesses to the block by all cores. This way, these protocols send requests directly to the owner cache, thus avoiding the indirection caused by accessing a separate directory (usually in the home node). A hints mechanism ensures a high hit rate when predicting the current owner of a block for sending requests, but at the price of significantly increasing network traffic, and consequently, energy consumption. In this work, we show how using a heterogeneous interconnection network composed of two kinds of links is enough to drastically reduce the energy consumed by hint messages, obtaining significant improvements in energy efficiency.